Corporate Governance Country Assessment : Moldova - World Bank (Washington, DC, 2013)
This report provides an assessment of Moldova's corporate governance framework-its legal and policy framework, as well as enforcement and compliance practices. The report makes policy recommendations where appropriate, and provides investors with a benchmark to compare corporate governance with the 1999 OECD Principles of Corporate Governance. Moldova is beginning to upgrade its legal and regulatory framework to meet international corporate governance standards. The report suggests that the main challenges will be to: (1) strengthen the legal requirements for shareholders to disclose their ultimate ownership and control positions, remove the authority of boards to increase capital without shareholder approval; establish clear liability and duties for board members, and require annual independent audits for joint stock companies; (2) increase the resources available to the NSC, and focus its enforcement efforts on transparency and disclosure, especially the disclosure of ownership, and the NSC's own transparency and accountability; (3) draft a corporate governance code to build awareness of corporate governance and to further clarify the responsibilities of the board; and (4) establish a training program on corporate governance to assist in building a shareholder culture in Moldova.